Persimmon Psylla, Trioza diospyri (Ashmead) (Insecta: Hemiptera: Psyllidae) - Frank W. Mead (EDIS)
EENY-390, a 4-page illustrated fact sheet by F. W. Mead, describes this insect, common and widely distributed in Florida and the southeastern United States, which occasionally causes moderate to severe damage to the leaves of wild and cultivated persimmon trees. Includes selected references. Published by the UF department of Entomology and Nematology, September 2006.